2013
DOI: 10.1074/jbc.m113.511014
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 3A Kinase Activity Is Regulated by Phosphorylation of the Kinase Domain Activation Loop

Abstract: Background: Class III myosins contain both a motor and kinase domain. Results: Phosphorylation of the kinase activation loop enhances MYO3A kinase activity, augmenting autophosphorylationinduced attenuation of motor and cellular activity. Conclusion: MYO3A kinase activity mediates localization and function within actin protrusions. Significance: Characterizing MYO3A kinase regulation enhances our understanding of the role of MYO3A in the maintenance of actin protrusions found in sensory epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 54 publications
(81 reference statements)
2
39
0
Order By: Relevance
“…However, this kinase is also autophosphorylated on multiple sites (Kozlov et al, 2006(Kozlov et al, , 2011. Myosin IIIa, briefly mentioned in Section 4.1.2, is phosphorylated by its increased concentration (Quintero et al, 2010(Quintero et al, , 2013. However, as its concentration is increased at filopodial tips, a relatively small region, the model geometry used in Section 3 is not appropriate.…”
Section: The Modelling Can Be Adapted To Model Specific Systemsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, this kinase is also autophosphorylated on multiple sites (Kozlov et al, 2006(Kozlov et al, , 2011. Myosin IIIa, briefly mentioned in Section 4.1.2, is phosphorylated by its increased concentration (Quintero et al, 2010(Quintero et al, , 2013. However, as its concentration is increased at filopodial tips, a relatively small region, the model geometry used in Section 3 is not appropriate.…”
Section: The Modelling Can Be Adapted To Model Specific Systemsmentioning
confidence: 97%
“…Examples include Myosin IIIa (Quintero et al, 2010(Quintero et al, , 2013) (a motor protein that binds actin and localises to filopodial tips), Ataxia Telangiectasia Mutated (ATM) Kinase (Bakkenist and Kastan, 2003;Kozlov et al, 2006Kozlov et al, , 2011Goodarzi et al, 2004;Ali et al, 2004) (an enzyme that is activated by DNA double-strand breaks), and p21 Activated Kinase 2 (PAK2) (Benner et al, 1995;Tuazon et al, 1997;Zenke et al, 1999;Wu and Wang, 2003;Jung and Traugh, 2005;Wang and Wang, 2008) (a protein that responds to several stress signals). In order to model any one of these systems explicitly, it may be necessary to incorporate other reactions specific to the system in question.…”
Section: The Model May Be Extended and Adaptedmentioning
confidence: 98%
See 1 more Smart Citation
“…The vertical black lines represent IQ motifs. MYO3A tail magnified diagram shows that the exon 30-amino acid sequence length is greater than that of combined sequences of exons [31][32][33][34] Examining the properties of the tail domain of MYO3 has improved our understanding of MYO3 motor-based transport and its interactions with cargo. We demonstrated that the conserved THD1 of MYO3 binds to both ESPN1 and ESPNL (6,26,32) (34).…”
Section: Figure 1 Diagrammatic Representation Of the Domain Structurmentioning
confidence: 99%
“…As has been shown, wild-type MYO3A induces filopodial actin protrusions and localizes to their tips, particularly well when its kinase domain was removed ([Salles et al, 2009] ; Fig. 3A), since its kinase activity autoregulates its motility, transport, filopodia tip accumulation rate, and actin bundle formation and stability [Quintero et al, 2010[Quintero et al, , 2013. In all our experiments, we used a construct encoding for Cherry-tagged MYO3A containing the p.Gly488Glu mutation lacking its kinase domain (Ch-MYO3A-K p.Gly488Glu) to accurately visualize the impact of the p.Gly488Glu mutation on motility and filopodia tip accumulation while eliminating any interference of autophosphorylation events on its filopodia transport rate.…”
Section: Characterization Of the Effect Of Pgly488glu Mutation On Mymentioning
confidence: 99%